2006
DOI: 10.1093/jac/dkl199
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of aerobic and facultatively anaerobic Gram-negative bacilli isolated from patients with intra-abdominal infections worldwide: 2004 results from SMART (Study for Monitoring Antimicrobial Resistance Trends)

Abstract: Antimicrobial resistance among GNB isolated from intra-abdominal infections continued to be a problem worldwide in 2004, with the highest rates of resistance overall in the Asia/Pacific region. The carbapenems and amikacin were the most consistently active agents in vitro against Enterobacteriaceae isolated from intra-abdominal infections worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
86
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 10 publications
8
86
2
4
Order By: Relevance
“…The Europe (Northern and Southern) in the SMART study with only 17% ESBL-producers Klebsiella spp. 6 Data from the MYSTIC study from South America showed 52% of resistance to cefepime, which can be a surrogate for ESBL strains. 7 Use of beta-lactam antibiotics containing an oxyimino group (cefuroxime, ceftriaxone, cefotaxime, ceftazidime, or aztreonam) are risk factors for ESBL-KP.…”
Section: Resultsmentioning
confidence: 99%
“…The Europe (Northern and Southern) in the SMART study with only 17% ESBL-producers Klebsiella spp. 6 Data from the MYSTIC study from South America showed 52% of resistance to cefepime, which can be a surrogate for ESBL strains. 7 Use of beta-lactam antibiotics containing an oxyimino group (cefuroxime, ceftriaxone, cefotaxime, ceftazidime, or aztreonam) are risk factors for ESBL-KP.…”
Section: Resultsmentioning
confidence: 99%
“…Esta cifra está dentro de lo esperable en base a estudios previos, si bien la frecuencia es muy variable en la literatura médica con variaciones regionales marcadas 19 . El estudio SMART que reunió 6.156 cultivos de infecciones intra-abdominales por bacilos gramnegativos en 28 países, incluido Latinoamérica, mostró una prevalencia en el caso de microorganismos productores de BLEE de 17% para K. pneumoniae y 10% para E. coli 20 .…”
Section: Discussionunclassified
“…The presence of these pathogens in the bowel is considered to be a risk factor for infections with these bacteria (28). Moreover, it can explain the high rates of isolation of ESBL-producing organisms in certain anatomic locations (i.e., abdominal and urinary tract infections) compared to the rates seen in others where there is not a clear indication of the presence of endogenous microbiota (28). It is of note that our 70% figure is similar to that seen with hospitalized patients under high antimicrobial selective pressure (17,23).…”
mentioning
confidence: 99%
“…It is of note that our 70% figure is similar to that seen with hospitalized patients under high antimicrobial selective pressure (17,23). Around 50% of our patients received antimicrobial treatment (18 patients) or medical assistance outside of the hospital setting (22 patients) at least 2 months before incurring ESBL infections; those conditions have been defined as risk factors for colonization with these pathogens (28).…”
mentioning
confidence: 99%